Interconnection of indicators of physical fitness of students of pedagogical specialties - Andrii Yefremenko; Svetlana Bliznyuk; Victoria Klimenchenko; Galeeva Valeria; Olena Nasonkina (Kharkiv State Academy of Physical Culture, 2019)
The results of determining the level of students' physical fitness according to generally accepted tests and the problems of implementing an effective process of physical education in higher education institutions of a pedagogical profile are presented. Purpose: to determine the strength of the correlation between the test indicators that determine the level of physical fitness of student teachers. Objects: Students of pedagogical specialties: 213 girls (I course - 136, III course - 77) and 34 children (I course - 21, III course - 13). Methods: Analysis of scientific and methodological sources; pedagogical testing; correlation analysis. Results: There has been a reduction in the number of students (boys and girls) who regularly attend physical education classes. It was revealed that the level of physical fitness according to the results of most test exercises decreases during study. The heterogeneity of the results of most tests is observed, which indicates their motor complexity for the level of physical fitness of students who took part in the study. Conclusions: A detailed development of measures is needed to increase motivation and value orientations towards regular physical activity of students of pedagogical specialties, an individual group approach to the development of physical education programs.